An Analysis of the Falsification Criterion of Karl Popper: A Critical Review - Mitra, Suddhachit (Tattva Journal of Philosophy, 2020)
Karl Popper identified ‘falsifiability’ as the criterion in demarcating science from non-science. The method of induction, which uses the (debated) principle of uniformity of nature, was rejected by Popper. He instead suggested that a scientific theory cannot be ‘verifiable’ but only ‘falsifiable’; one counter-example to the claims made by the theory would falsify it. The paper conducts a survey of the extant literature to understand the concept, the methodology as suggested by Popper to operationalize the concept, and possible limitations, both conceptual and methodological. The extant literature points out inherent ambiguities in the Popperian concept of falsifiabilty. One recurring theme is that Popper, the deductivist, uses the much critiqued inductivistic method among his methodological suite.